Teaching quality attributes from the perspective of undergraduate accounting students in Saudi Arabia: a survey - Ebaid, Ibrahim El-Sayed (Journal of Management and Business Education, 2023)
This study aims to explore the attributes of teaching quality from the perspective of undergraduate accounting students in Saudi Arabia. A questionnaire survey was used to obtain views of undergraduate accounting students on the attributes of teaching quality. 28 attributes of teaching quality were included in the questionnaire. The findings of the study showed the importance of 27 of the 28 attributes of teaching quality included in the questionnaire from the accounting students' perspective. These attributes include attributes related to the class preparation and design, the class delivery, and the instructor's traits and personal characteristics. The findings of the study can help accounting faculties to evaluate their teaching strategies and create a development plan that is aligned with students’ expectations to enhance teaching quality, improve classroom effectiveness, and ultimately deliver students who are better prepared for the accounting profession. The findings of the study may also be of interest to academic managers, such as deans and heads of departments/schools, in designing staff development programs to improve teaching and student satisfaction. This study is timely because most of the undergraduate accounting programs in Saudi universities have recently applied for accreditation either from national or international accreditation bodies. As teaching quality is one of the important factors in obtaining academic accreditation, this study may have important implications in the field of higher education in Saudi Arabia.